A Critical Political Economy Perspective on Indian Television: STAR, Hotstar, and Live Sports Streaming - Mahima Singh; Akshaya Kumar (tripleC: Communication, Capitalism & Critique)
The Indian television industry is transforming via an increasing number of Over-the-Top (OTT) platforms. This shift from broadcast to OTT has given rise to research assessing the impact on the television ecosystem. With the case of Star Network, this study examines how the emergence of live sports streaming has affected the power dynamics in the sports broadcasting ecosphere. This study employs the Critical Political Economy framework to address the following question: How do television-based media conglomerates – and by extension television itself – negotiate the challenge of Internet-based digital media in India? Keeping the focus on sports live-streaming services, we study the transition from Star television network to Disney+ Hotstar, its corresponding OTT platform. We however argue that the Political Economy of Communication holds its ground despite the apparently disruptive promise of web-based platforms. Despite the Internet posing new challenges in terms of distribution networks, media conglomerates find a way to convert their dominance of the television industry into the OTT space.